Financial assets, debt, and liquidity crises : a Keynesian approach - Charpe, Matthieu (Cambridge University Press, 2011)
"The macroeconomic development of most major industrial economies is characterised by boom-bust cycles. Normally such boom-bust cycles are driven by specific sectors of the economy. In the financial meltdown of the years 2007-2009 it was the credit sector and the real-estate sector that were the main driving forces. This book takes on the challenge of interpreting and modelling this meltdown. In doing so it revives the traditional Keynesian approach to the financial-real economy interaction and the business cycle, extending it in several important ways. In particular, it adopts the Keynesian view of a hierarchy of markets and introduces a detailed financial sector into the traditional Keynesian framework. The approach of the book goes beyond the currently dominant paradigm based on the representative agent, market clearing and rational economic agents. Instead it proposes an economy populated with heterogeneous, rationally bounded agents attempting to cope with disequilibria in various markets"-- Provided by publisher.